COMACO, from snares to plowshares: A conservation and human wellbeing success story. Issue 10 (14th September 2020) - Lewis, Dale; Wilkie, David S.
Abstract: Community Markets for Conservation is a private sector, not‐for‐profit social enterprise in Zambia. It was established in 2003 to halt wildlife poaching and illegal tree cutting for charcoal by helping poor rural families to increase their food and income security through improved farming practices and marketing of value‐added agricultural commodities. COMACO supports 178, 891 farmers in the Luangwa Valley, providing them with improved farming skills, seed loans, a premium price for their crop surplus, and a dividend if they comply with sustainable farming and wildlife, and forest conservation best practices. Maize yields using COMACO methods increased by 63% and net income was 37% higher than for farmers who purchased inorganic fertilizers. Between 2012 and 2018 the number of food secure families increased from 67–84%. Elephant poaching has declined in all but one COMACO district, poaching is now primarily conducted by nonlocal hunters, and leg‐hold snare detections by community game scouts have decreased significantly in COMACO areas. Increasing food and income security while reducing deforestation and unsustainable hunting for US10 per farmer per year is cheap and can be replicated in Zambia and other nations in Africa.